Textbook of Allergen Tolerance - Klimov, Vladimir V.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Allergies are a significant health issue, yet few books exist on allergen tolerance of separation; here the author classifies allergen tolerance breakdown in specific types, according to the possibility that the autonomic breakdown of allergen tolerance in the unified airway depends on a deficit of pro-tolerogenic neurotransmitters at the local level. This paradigm, which explains the pathogenesis of allergic disorders, opens to new approaches to allergen-specific immunotherapy (AIT). While focusing on the new atopic disorders of the unified airway, such as local allergic rhinitis, "dual" allergic rhinitis, local allergic asthma, and local allergic conjunctivitis, the work combines clinical examples of allergic diseases and their treatment with their immunological background. The topics range from the specific immune-derived maintenance of allergen tolerance and the role of the neuroimmune network in allergic inflammation to conventional atopic diseases and more particular issues of local atopic disorders in the unified airway, oral tolerance, and its breakdown, and its translation in genitourinary aspects of allergic inflammation. Specific chapters are also devoted to allergen-specific immunotherapy (AIT) and anti-allergy treatments. Thought for upper graduate students, it will also be a valued resource for allergy practitioners, pulmonologists, ENT specialists, pediatricians, and translational researchers, Textbook of Allergen Tolerance includes classical didactic features such as abstracts, keywords, background notes, discussion points, and Q&A., as well as 20 audio files Text-to-Speech for the visually impaired, and 10 video to support the readers. .
Chapter 1) Antigens and Allergens -- Chapter 2) Immune Tolerance at a Glance -- Chapter 3) Immune-Derived Maintenance of Allergen Tolerance -- Chapter 4) The Role of the Neuroimmune Network in Allergic Inflammation -- Chapter 5) Conventional Atopic Diseases -- Chapter 6) Local Atopic Disorders in the Unified Airway -- Chapter 7) Food Allergies and Oral Tolerance -- Chapter 8) Allergen-Specific Immunotherapy (AIT) -- Chapter 9) Allergen Tolerance in the Genitourinary Tract -- Chapter 10) Allergies in Covid-19 and Post-Covid Syndrome.
Keywords: Allergy; Immunology; Allergology; Immunology; Allergens; Hypersensitivity; Allergy and Immunology; Immune Tolerance; Handbook